Aerobic exercise strategies for anxiety and depression among children and adolescents: a systematic review and meta-analysis - Huishan Song; Sheng Ge; Yuhe Wang; Linghua Ran; Hongyan Zhang (Frontiers in Public Health)
ObjectiveThis study aimed to investigate the effects of exercise intensity, frequency, session duration, and intervention period in aerobic exercise programs on alleviating depression and anxiety symptoms among children and adolescents. The objective of this study is to develop suitable aerobic exercise plans for these individuals.MethodsAll articles published between the database inception year and November 2024 were obtained from PubMed, Scopus, and Web of Science. A meta-analysis was conducted using RevMan 5.4.ResultsThe analysis included data from 19 randomized controlled trials involving 2,093 children and adolescents. The findings indicated that aerobic exercise significantly improved anxiety (standardized mean difference [SMD] = −0.32, 95% CI: −0.60, −0.03; p < 0.00001) and depression (SMD = −0.64, 95% CI: −0.94, −0.33, p < 0.00001). For anxiety symptoms, sessions lasting 60–75 min showed significant effects (SMD = −1.65, 95% CI: −3.25, −0.06, p < 0.00001); a frequency of 3–4 sessions/week was most effective (SMD = −0.42, 95% CI: −0.74, −0.10, p = 0.001); and interventions exceeding 12 weeks showed significant improvements (SMD = −0.51, 95% CI: −0.89, −0.14, p = 0.002). For depression symptoms, sessions lasting 60–75 min produced significant effects (SMD = −0.78, 95% CI: −1.24, −0.33, p = 0.001); a frequency of 3–4 sessions/week yielded optimal outcomes (SMD = −0.78, 95% CI: −1.09, −0.46, p < 0.00001); and a shorter duration of 5–8 weeks showed significant improvements (SMD = −1.22, 95% CI: −1.79, −0.65, p < 0.0001).ConclusionFor managing anxiety symptoms in children and adolescents, we recommend a high-intensity exercise regimen (60–89% VO2 max, 60–75 min/session, 3–4 sessions/week) with an optimal intervention duration of over 12 weeks. For managing depression symptoms, we propose a moderate-to-high-intensity exercise protocol (40–89% VO2 max) with the same session duration and frequency, but with a shorter optimal intervention duration of 5–8 weeks.